INTERACTIVE FEFFECT OF LIGHT INTENSITY AND HYDRO- AND HALO PRIMING, USING SOME K- AND Mg-SALTS, ON FLORAL ATTRIBUTES AND PRODUCTIVITY OF TWO GENOTYPES OF WHEAT (Triticum aestivum L.) (Applied Biological Research, 2024)
Seed priming cause invigoration of seeds in this process the seed grains are  allowed to soak moisture till a period before protrusion of radicle (safe limit).  When soaking medium is water it is called hydropriming and when salt solutions  is used it called halopriming. In priming, the seeds are dried back to original  moisture content after soaking till safe limit. In present study, a comparative  study on the effect of interaction of hydro- and halo-priming on two genotypes  (WR-544 and DBW-187) of wheat were studied for impact on floral attributes  and productivity. Distilled water was used for hydro-priming and 0.5, 1.0 and  1.5% of KCl, KH2PO4, Mg(NO3)2 and MgSO4 salt solutions were used for hydro priming. The study revealed that floralinitiation took in just 43 days in ‘WR 544’ under 1.5% Mg(NO3)2 + 100% light treatment and 1.5% MgSO4 + 50%  light treatment; whereas it took place in 60 days under 1.0% KH2PO4 + 50%  light treatment. In genotype ‘DBW-187’, flowering took place in 56 days under  hydro-priming + 100% light as well as 50% light interacted with hydro-priming  or halo-priming with 0.5% KCl. In genotype ‘WR-544’ the viable grains in 1.5%  Mg(NO3)2 + 100% light treatment were 377. In both genotypes halo-priming  improved productivity. In genotype WR-544, 388 spikelets were produced under  100% light + 1.5% Mg(NO3)2 treatment. The genotype WR-544 appeared better  performer than DBW-187 under both priming conditions.
Keywords: Floral initiation; hydropriming; halopriming; interaction,; spikelets; viable grains